Young people’s happiness in the context of negative life events and coping strategies: a latent profile and latent class analysis - Sema Polatcı; Ömer Lütfi Antalyalı; Ali Murat Alparslan; Seher Yastıoğlu (BMC Psychology, 2023)
Abstract Young people have to cope with many negative life events and stress factors to maintain their happiness. Although there are studies on how they benefit from different coping strategies and their results, there is no study that profiles/groups young people according to negative life events and coping styles. From this point of view, the study aims to determine different life events classes and stress coping profiles in young people, and to examine the differences in happiness among the new groups created according to the discovered classes and profiles. Participants consisted of 1093 young people (M = 21.08) from different state universities in Turkey. Latent profile analysis (LPA) was conducted, resulting in a 3 profile solution characterizing coping strategies: Positive-oriented (26.8%), slightly positive-oriented (50%), and negative-oriented (23.2%) coping strategy profiles. Latent class analysis (LCA) was conducted, resulting in a 2 class solution characterizing negative life events: More negative (40.1%) and less negative (59.9%) life events classes. For the purpose of the study, the profiles created with the latent profile analysis and the latent class analysis were considered together and the participants were divided into 6 groups. These groups differed significantly in terms of happiness. The group with the highest level of happiness is the group with positive-oriented coping strategies and less negative life conditions (μ = 4.35, p < .001), and the group with the lowest level of happiness is the group with negative-oriented coping strategies and more negative life conditions (μ = 3.48, p < .001). However, the findings indicated that a positive-oriented coping strategy profile (the profile that scored high on positive coping strategies and low on negative coping strategies) offers the most promising route to happiness whether experienced negative life events are less or more.